Dinasti Mamalik di Mesir: Pembentukan, Kemajuan dan Kemunduran - Almahdali, Sayyid Syahdan; S, Sukamto; Sulaiman, Umar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Mamluk Dynasty, which ruled Egypt from 1250 to 1517, was founded by military slaves (mamluks) originally from regions such as the Caucasus. Despite their origins as slaves, the mamluks rose to power and established a strong political, economic, and cultural civilization. The dynasty's rise began after the death of Sultan al-Malik al-Salih, when his son Sultan Turan Shah's reign was overthrown by the mamluks, leading to the ascension of Syajarah al-Dur, the first female ruler of the Mamluk Sultanate. The Mamluks secured military victories, including the Battle of Ayn Jalut against the Mongols, which significantly contributed to the stability of the region. They also advanced the economy through trade, agriculture, and efficient irrigation techniques. Culturally, the Mamluks left a lasting legacy in architecture, building grand mosques and educational institutions. However, internal divisions, external threats from the Ottoman Empire, economic decline, and corruption eventually led to the fall of the dynasty in 1517. The Mamluk Dynasty’s period is a testament to the rise of an elite military class and their influence in shaping Islamic civilization during their rule.